OP0273 ADHERENCE TO COLCHICINE TREATMENT AND COLCHICINE RESISTANCE IN A MULTICENTRIC FMF NATIONAL COHORT. (2nd June 2020) - Gallizzi, R.; Bustaffa, M.; Mazza, F.; Sutera, D.; Fabio, G.; Obici, L.; Alessio, M.; Rigante, D.; Cantarini, L.; Insalaco, A.; Cattalini, M.; Maggio, M. C.; et al.
Abstract : Background: Colchicine is the standard treatment for Familiar Mediterranean Fever (FMF), however about 5% of patients experience colchicine resistance. There is no standard definition of colchicine resistance. Recently a panel of experts elaborated a new definition based on a Delphi consensus approach. Objectives: We aim to describe main features of the disease and clinical outcome of a cohort of FMF patients with particular interest on the colchicine resistance and tolerability according to the definitions proposed by the recent consensus. Methods: Since November 2009, 425 Italian pediatric and adult FMF patients (pts) from 13 centers were enrolled in a national longitudinal cohort study, using the international EUROFEVER registry. Demographic, genetic and clinical data, including response to treatment, were analyzed. Supplementary information on health related quality of life and treatment adherence was also collected by a specific questionnaire. Results: Complete information were available in 341 pts (189 M and 152 F, 211 children and 120 adults). The median age at disease onset was 5.0 years (1 m-59 y); the mean diagnostic delay was 8.7 y (range 0-61 y). The median age at enrollment was 12.1 y (range 3 m - 82 y). The MEFV genotype was the following: 103 (30.2%) pts carried biallelic pathogenic variants; 59 (17.3%) one pathogenic variants and one VOUS /LB variant; 27 (7.9%) had biallelic VOUS/LB variants; 97 (28.45%) were heterozygous for pathogenic variants; 30 (8.8%) were heterozygous for VOUS/LB, 25 (7.33%) were genetically negative. Colchicine treatment was used in 280 pts; during treatment, biologic treatment (anti-IL1) in 22 pts. 61 pts received NSAID or steroid on demand. We analyzed the behavior of the pts treated with colchicine according to the statements on colchicine resistance/intolerance defined by Ozen et al (1) (Table 1 ). Conclusion: Almost 58% of FMF pts display disease activity despite colchicine treatment. The treatment is generally under-dosed, especially in children. The adherence and the compliance to the treatment is generally good. References: [1]Ozen S et all. Recommendation on colchicine dosing and definition of colchicine resistance/intolerance in the management of FMF. Pediatric Rheumatology, 2019. Acknowledgments: This research was financial supported by Novartis AG Disclosure of Interests: Romina Gallizzi: None declared, Marta Bustaffa: None declared, Francesca Mazza: None declared, Diana Sutera: None declared, Giovanna Fabio: None declared, Laura Obici: None declared, Maria Alessio: None declared, Donato Rigante: None declared, Luca Cantarini: None declared, Antonella Insalaco: None declared, Marco Cattalini: None declared, Maria Cristina Maggio: None declared, Gabriele Simonini: None declared, Alma Nunzia Olivieri: None declared, Serena Pastore: None declared, Maddalena Lancieri: None declared, Nicolino Ruperto Grant/research support from: Bristol-Myers Squibb, Eli Lily, F Hoffmann-La Roche, GlaxoSmithKline, Janssen, Novartis, Pfizer, Sobi (paid to institution), Consultant of: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lily, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi, Takeda, Speakers bureau: Ablynx, AbbVie, AstraZeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lily, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, Sanofi, Servier, Sinergie, Sobi, Takeda, Marco Gattorno Consultant of: Sobi, Novartis, Speakers bureau: Sobi, Novartis